Comparative efficacy of GLP-1 RAs/SGLT-2 inhibitors in reducing cardiovascular events in type 2 diabetes according to baseline use of metformin: a systematic review and meta-analysis of randomized controlled trials - Yuxin Zhang; Zhaoji Li; Yongchen Hao (European Journal of Medical Research)
Abstract Background Sodium–glucose transporters 2 inhibitors (SGLT-2i) and glucagon-like peptide 1 receptor agonists (GLP-1 RAs) are recommended along with metformin for the potential cardiovascular benefits among type 2 diabetes. This meta-analysis aims to evaluate whether the effects of SGLT-2i or GLP-1 RAs on cardiovascular outcomes are consistent with and without baseline metformin use. Methods PubMed, Cochrane, Web of Science and Embase were searched for randomized placebo-controlled trials with SGLT-2i or GLP-1 RAs as interventions of type 2 diabetes patients up to June, 2024. The main outcomes were major adverse cardiovascular events (MACE), hospitalization for heart failure (HHF) or cardiovascular death. Both random-effects model and fixed model were adopted to estimate pooled hazard ratios (HR) and 95% confidence intervals (95% CI). Results A total of 81,738 patients (median age: 62–66 years, 53.7–71.5% men, median follow-up: 1.3–5.4 years) from 11 studies (7 studies of SGLT-2i and 4 of GLP-1 RAs) were included in the study. The metformin-naive portions ranged from 28.90% to 81.98%. Among patients using metformin at baseline, SGLT-2i or GLP-1 RAs reduced MACE risk (HR = 0.95, 95% CI 0.91–0.99, P = 0.02). In metformin-naive patients, similar reductions were observed (HR = 0.79, 95% CI 0.65–0.95, P = 0.01). No statistically significant interaction was found between metformin users and non-users for any outcome (all P values for interaction > 0.05), indicating consistent cardiovascular benefits regardless of baseline metformin therapy. Conclusions SGLT-2i and GLP-1 RAs have the effects of cardiovascular benefits for T2DM patients regardless of baseline metformin use.